Self-reflections across the adult lifespan: associations with personality traits in a binational sample - Küchler, Gabriela; Borgdorf, Kira Skirwitt Ann; Aguilar-Raab, Corina; Wrzus, Cornelia (Self and identity, 2025)
Age differences in personality-related self-reflections are scarcely studied despite their potential to explain normative personality development. The present research investigated how age and personality trait levels are associated with general and trait-specific self-reflections (e.g. exploration, comparisons) in a binational sample from the United States and Germany (N = 615, 18-84 years) using a broad range of questionnaires. Overall, self-reflections were less pronounced with older age. Individuals with higher trait levels compared themselves less regarding the respective trait, and some trait-specific comparisons (e.g. comparing oneself to others regarding emotional stability) were even more closely linked to trait levels with older age. We discuss how age differences in self-reflections could contribute to trait development across the lifespan.